Investigation of Amino Acids As Herbicides for Control of Orobanche minor Parasitism in Red Clover - Fernández-Aparicio, Mónica; Bernard, Alexandre; Falchetto, Laurent; Marget, Pascal; Chauvel, Bruno; Steinberg, Christian; Morris, Cindy E.; Gibot-Leclerc, Stephanie; Boari, Angela; Vurro, Maurizio; Bohan, David A.; Sands, David C.; et al. (Frontiers in Plant Science, 2017)
Certain amino acids induce inhibitory effects in plant growth due to feedback inhibition of metabolic pathways. The inhibition patterns depend on plant species and the plant developmental stage. Those amino acids with inhibitory action on specific weeds could be utilized as herbicides however their use for weed control has not been put into practice. Orobanche minor is a weed that parasitizes red clover. O. minor germination is stimulated by clover root exudates. The subsequent seedling is an obligated parasite that must attach quickly to the clover root to withdraw its nutrients. Early development of O. minor is vulnerable to amino acid inhibition and therefore, a series of in vitro, rhizotron and field experiments were conducted to investigate the potential of amino acids to inhibit O. minor parasitism. In in vitro experiments it was found that among a collection of 20 protein amino acids, lysine, methionine and tryptophan strongly interfere with Orobanche minor early development. Field research confirmed their inhibitory effect but revealed that methionine was more effective than lysine and tryptophan, and that two successive methionine applications at 308 and 543 growing degree days inhibited O. minor emergence in red clover up to 67%. We investigated additional effects with potential to influence the practical use of amino acids against broomrape weeds, whether the herbicidal effect may be reversible by other amino acids exuded by host plants or may be amplified by inducing host resistance barriers against O. minor penetration. This paper suggests that amino acids may have the potential to be integrated into biorational programs of broomrape management.